Pengaruh kualitas produk, harga dan promosi terhadap keputusan pembelian - Prayogo, Bagus Agung (Universitas Mercu Buana, 2025)
Judging from the growth of this creative business, more and more types of businesses are popping up in Indonesia, especially in Yogyakarta. As a business in the creative field, Ciko's studio must be stronger and dare to compete against similar hampers businesses. Thus, the Ciko study must try its best to be able to improve consumer purchasing decisions including product quality, price and promotion as factors that are considered influential. The purpose of this research is to analyze and find out the influence of Ciko Studio consumer purchasing decisions on product quality, price and promotion variables. The object of this research is consumers who have bought Ciko's Studio hampers at least once. This research was conducted on 152 respondents using quantitative descriptive. The approach used in this study is the Structural Equation Model (SEM) with the Smart-PLS analysis tool. By using a quantitative descriptive approach, the results of this study indicate that product quality, price and promotion have a positive and significant impact on consumer purchasing decisions at Ciko Studio.